Performance practice in the Baroque era interest session (Los Angeles : V & S Video Productions, 2000)
Muestra la presentación pública de un coro interpretando música barroca
Presiding, William Hatcher ; Clinician, Denis Shrock San Jose Choral project Daniel Hughes, conductor
Keywords: MUSICA CORAL; MUSICA BARROCA